(untitled) (Baghdad Science Journal, 2025)
The crude cell wall of E.cloacae was extracted by using Lysozyme , DNase and RNase enzymes, the contents of the proteins and carbohydrates were 24% and 1.44% respectively . The pathogenicity of the bacteria was studied by testing its lethality, in which the LD50 was identified to both bacterial suspension and the extract of the crude cell wall of bacteria by using white swiss female mice. The value of the LD50 of bacterial suspension was 3.16x109 CFU / ml . The cell wall extract didn’t have any lethal effect on the mice, but it had a great effect on their physiological state which led to a deficit in their weight by an average of 8 grams.